Application of LSVT BIG Intervention to Address Gait, Balance, Bed Mobility, and Dexterity in People With Parkinson Disease: A Case Series. Issue 7 (1st July 2014) - Janssens, Jorina; Malfroid, Klaartje; Nyffeler, Thomas; Bohlhalter, Stephan; Vanbellingen, Tim
Abstract : Background and Purpose: Lee Silverman Voice Treatment Big (LSVT BIG) is characterized by intensive exercising of high-amplitude movements to overcome bradykinesia and hypokinesia in patients with Parkinson disease (PD). The aim of the present case series was to explore possible beneficial effects of LSVT BIG training on gait, balance, bed mobility, and dexterity. Case Description: Three patients with mild to moderate PD (all male; aged 52, 54, and 70 years; Hoehn & Yahr stages I–III) completed a 4-week LSVT BIG training program (16 individual 1-hour sessions) and an intensive home training program in accordance with the LSVT BIG protocol. Two certified LSVT BIG physical therapists delivered the LSVT BIG training sessions. Outcomes: The outcome measures for gait and balance included the Functional Gait Assessment (FGA), Functional Reach Test (FRT), Timed "Up & Go" Test (TUG), Freezing of Gait Questionnaire (FOGQ), and motor score on part III of the Unified Parkinson's Disease Rating Scale (UPDRS III). Bed mobility was addressed using the Lindop Parkinson's Disease Mobility Assessment (LPA). The Nine-Hole Peg Test (9HPT) was used to measure dexterity. The 3 patients performed better on balance and gait assessments, as indicated by increased scores on the FRT and FGA (all 3 patients) and decreased scores on the TUG, FOGQ, and UPDRS III, of which scores of the FRT and UPDRS III achieved the minimal detectable change. Furthermore, the patients were quicker in tasks related to bed mobility (LPA). The patients' dexterity skills did not improve for their dominant (right) hand (9HPT). Discussion: This case series suggests that the LSVT BIG may be beneficial for gait, balance, and bed mobility. Future work is needed to ascertain the effectiveness by means of randomized controlled trials.